1994
DOI: 10.1161/01.str.25.9.1752
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of stroke among inpatients in a large Italian hospital.

Abstract: Background and PurposeThe incidence of stroke among inpatients is not known. The aim of our study was to investigate the incidence of stroke not preceded by evident iatrogenic factors such as surgical or medical procedures in a cohort of inpatients in a large Italian general hospital.Methods From January 1, 1992, to December 31, 1992, we evaluated patients referred to our neurology department with a suspected diagnosis of stroke that occurred during hospitalization. Patients presenting with stroke as a complic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
21
0
2

Year Published

2001
2001
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 11 publications
1
21
0
2
Order By: Relevance
“…Our study involved the prospective identification of a relatively large number of IHS cases from a broadly representative population of statewide hospitals, and therefore differs from several of the previous reports that were based on a limited number of cases and/or hospitals [2, 3, 25]. This study confirmed previous findings that cardiovascular, neurological, and neurosurgical disorders were the most common admitting diagnoses among patients who went on to develop IHS.…”
Section: Discussionsupporting
confidence: 82%
“…Our study involved the prospective identification of a relatively large number of IHS cases from a broadly representative population of statewide hospitals, and therefore differs from several of the previous reports that were based on a limited number of cases and/or hospitals [2, 3, 25]. This study confirmed previous findings that cardiovascular, neurological, and neurosurgical disorders were the most common admitting diagnoses among patients who went on to develop IHS.…”
Section: Discussionsupporting
confidence: 82%
“…Therefore, approximately 1 of 25 stroke patients had an in-hospital stroke onset. Azzimondi et al [1] reported that the stroke incidence rate among hospitalized patients was 11.08/1,000 per year, which was higher than that reported in community-based studies. In the present study, since we did not determine the number of in-hospital patients for each participating hospital, we could not calculate the incidence rate of in-hospital stroke.…”
Section: Discussionmentioning
confidence: 93%
“…The mechanism of in-hospital stroke has been reported to be due to iatrogenic causes, such as operative procedures, unsuccessful cardioversion, coronary angiography and to be associated with coronary artery diseases [1, 2]. However, the characteristics of in-hospital stroke have not been clearly elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…The crude incidence of stroke in hospitalized patients has been estimated at 11/1,000 [5] , compared to an incidence of 2/1,000 of stroke in the general population [6] . Ischemic stroke occurs in 0.1-0.3% of patients with myocardial infarction [7] and among patients with myocardial infarction, cardiac failure and atrial fibrillation have been identified as the most common predictors for ischemic stroke [8] .…”
Section: Introductionmentioning
confidence: 99%